Attachment‐Based Family Therapy as an Adjunct to Family‐Based Treatment for Adolescent Anorexia Nervosa. Issue 2 (10th June 2016) - Wagner, Ingrid; Diamond, Guy S.; Levy, Suzanne; Russon, Jody; Litster, Richard
Abstract : Adolescent anorexia nervosa (AN) has a significant and long‐standing impact for the health and well being of young people and their families. The determinants of illness are multi‐factorial, however, adolescent AN has been consistently associated with parental distress (e.g., depression, anxiety, alcoholism), family conflict, and low parental warmth toward the adolescent. Whilst Family Based Therapy (FBT) for adolescent AN is the recommended first line of treatment, a substantial proportion of patients do not experience remission by the end of therapy or may relapse following remission. Although a range of adjuncts to FBT have been proposed, no preferred model has emerged. In this paper, we compare and contrast Attachment‐Based Family Therapy (ABFT) with FBT, and argue that ABFT's focus on relationships, rather than behaviours, could make a substantive contribution to the practice of FBT. We present a case study to demonstrate how ABFT may help to alleviate some of the maintaining factors of adolescent AN through the repair of parent–child relational ruptures.